THE RESPONSE OF THE COMMUNITY TOWARDS THE DEVELOPMENT OF TOURISM IN TEBING BREKSI YOGYAKARTA - Indri Kurniawati; M Baiquni; Djoko Wiyono (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
The main focus of this research is to explain the community response of society in Sambirejo Village in developing tourism in Breksi Cliffs. Responses are assessed from three aspects namely: perception, attitude and participation. Data analysis is done by understanding and compiling data that has been collected systematically. The aim is to find the community’s response to tourism and the level of community participation in tourism management. The result of this study is two types of responses namely positive and negative. Positive response arises from people who want to take advantage of business opportunities, the formation of local institutions, and the change in status experienced by the management members of Breksi Cliffs. While the negative response arises from the group of miners who were directly affected by mine stop regulation. The miners reject the developing of tourism that they did not get a stable income if they work in the tourism industry.Keywords: Breksi Cliff, Community Response, Tourism Development, Geotourism